1997
DOI: 10.1097/00007890-199712150-00013
|View full text |Cite
|
Sign up to set email alerts
|

Infectivity of Hepatic Allografts With Antibodies to Hepatitis B Virus

Abstract: Hepatic allografts from donors positive only for anti-HBs do not transmit HBV infection. Hepatic allografts from anti-HBc-positive donors frequently transmit HBV infection to naive recipients regardless of the donor anti-HBs status, and antiviral prophylaxis may be indicated. Anti-HBs-positive recipients appear resistant to HBV infection after orthotopic liver transplantation with an allograft from an anti-HBc-positive donor. Recipients positive only for anti-HBc infrequently develop HBV infection when transpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
167
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(172 citation statements)
references
References 8 publications
5
167
0
Order By: Relevance
“…16 About 4% of liver donors are positive for HBcAb. 3 For recip- ients of livers bearing this marker, HBV has been reported to occur anywhere from 30% to 50% 6-8 to up to 78%. 9 This is concerning, because in the absence of therapy, HBV infection can progress to severe allograft dysfunction, graft loss, and even patient death.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…16 About 4% of liver donors are positive for HBcAb. 3 For recip- ients of livers bearing this marker, HBV has been reported to occur anywhere from 30% to 50% 6-8 to up to 78%. 9 This is concerning, because in the absence of therapy, HBV infection can progress to severe allograft dysfunction, graft loss, and even patient death.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Because of the severe shortage of organ donors, the transplant community has turned to the use of the so-called extended donors. Among this extended pool are those liver donors with hepatitis B core antibody (HBcAb)-positive serology but negative hepatitis B surface antigen (HBsAg), which can comprise up to 4% of all liver donors 3 ; however, it is unclear whether these organs should be used for transplant. 4,5 There have been documented instances of de novo occurrence of hepatitis B (HBV) infection in recipients of these organs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The potential sources of the infection include transfused blood products, occult donor-organ infection and occult pretransplant infection in the recipient. Blood products are occasionally able to transmit HBV despite negative serological testing [14] or past HBV infection [15,161, with an estimated risk for the latter of 33%-78% [17,18,19,201. In the present case two possible sources of HBV infection were identified: sexual transmission from the HBsAg-positive partner or occult transmission from the HBcAb-positive liver donor.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have documented a 33% to 78% increased incidence of HBV infection in HBV-naïve recipients of hepatic allografts from donors who were HBsAg negative, but positive for anti-HBc. 64,[76][77][78][79][80][81][82][83][84][85][86][87] Thus, some investigators have suggested that these organs could be safely directed to appropriate recipients, mainly those with anti-HBs and/or anti-HBc at the time of OLT. 64,77,84 The real impact of this recommendation on these transplant recipients has been formally evaluated only recently at the University of Pittsburgh.…”
Section: Anti-hbc-positive Donorsmentioning
confidence: 99%